Longitudinal Alterations of Retinal and Choroidal Structure in Patients Recovered from COVID-19 - Mojtaba Abrishami; Kiana Hassanpour; Ghodsieh Zamani; Seyedeh Maryam Hosseini; Nasser Shoeibi; Zahra Emamverdian; Amir Zamani; Nasibeh Amini; Majid Abrishami (Journal of Ophthalmology)
Objective. To evaluate the midterm longitudinal changes in chorioretinal structures in patients with coronavirus disease 2019 (COVID-19). Methods. Thirty-four eyes of 17 COVID-19 patients were enrolled. The patients underwent retinal and choroidal imaging upon the recovery (baseline) after 1 and 3 months. Retinal measurements in fovea, parafovea, and perifovea were recorded. To calculate choroidal vascularity index (CVI), luminal and total choroidal areas were measured using Sonada's method. Choroidal thickness was measured at the subfovea 500 microns temporal and nasal to the fovea. Results. Mean CVI was 0.64 ± 0.04 at baseline that significantly increased to 0.67 ± 0.05 (P = 0.012) after 1 month and again significantly decreased to 0.63 ± 0.05 after 3 months (P < 0.001). While the stromal component showed a significant decrease between the baseline and first-month values (1.16 ± 0.29 to 1.01 ± 0.27, P = 0.03), the luminal area mostly changed between months 1 and 3 (2.03 ± 0.28 to 1.91 ± 0.23, P = 0.045). The average of subfoveal choroidal thickness and retinal thickness remained unchanged. Conclusion. CVI is increased in patients with COVID-19 1 month after recovery from COVID-19 and returns to baseline values after 3 months. Regarding the reversible nature of changes, there might be a prominent role in inflammation.